Why older nurses leave the workforce and the implications of them staying. Issue 5 (19th December 2014) - Duffield, Christine; Graham, Elizabeth; Donoghue, Judith; Griffiths, Rhonda; Bichel‐Findlay, Jen; Dimitrelis, Sofia
<x xml:space="preserve">Abstract</x> Aims and objectives To identify factors that motivate older nurses to leave the workforce. Background As many older nurses are now reaching retirement age and will be eligible for government‐funded pensions, governments are concerned about the impending financial burden. To prepare for this scenario, many are looking at increasing the age of retirement to 67 or 70 years. Little is known about how this will affect the continuing employment of older nurses and the consequences for employers and the nurses themselves if they remain longer in the workforce. Design Prospective randomised quantitative survey study. Methods The Mature Age Workers Questionnaire, Job Descriptive Index and Job in General Scale were used to measure job satisfaction, intention to retire and factors encouraging retirement in registered nurses aged 45 years and over (n = 352) in Australia (July–August 2007). Results There were 319 respondents. The mean age proposed for leaving the workforce was 61·7 years. Key motivators were: financial considerations (40·1%), primarily financial security; nurse health (17·4%) and retirement age of partner (13·3%). Conclusions Older nurses are leaving the workforce prior to retirement or pension age, primarily for financial, social and health reasons, taking with them significant experience and knowledge. As financial considerations are important in older nurses decisions to continue to work, increasing the age of retirement may retain them. However, consideration will need to be given to ensure that they continue to experience job satisfaction and are physically and mentally able to undertake demanding work. Relevance to clinical practice Increasing retirement age may retain older nurses in the workforce, however, the impact on the health of older nurses is not known, nor is the impact for employers of older nurses continuing to work known. Employers must facilitate workplace changes to accommodate older nurses.